2021
DOI: 10.3390/ijerph18105348
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Professionals’ Message to Others: An Ethnographic Approach

Abstract: Introduction: Palliative care continues to be misunderstood within the world of healthcare. Palliative care professionals are key agents for promoting a greater understanding of their field. This study aims to examine the messages, both implicit and explicit, that palliative care professionals transmit about themselves and their work within their teams and to other health professionals. Methods: Focused ethnographic secondary analysis, exploring the interactions of palliative care professionals as it happens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One study indicated that participants with high (vs. low) actual knowledge were less likely to find palliative care fear-inducing or depressing and more likely to believe it offered hope [ 28 ]. It is essential that palliative care professionals perceive themselves as potential influencers and explicitly transmit the reasons for their intervention [ 29 ] while avoiding perpetuating myths, misunderstandings, and positive associations with a lack of palliative care. HPs should grasp the chance to carry out these sharing procedures when a decision is required.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that participants with high (vs. low) actual knowledge were less likely to find palliative care fear-inducing or depressing and more likely to believe it offered hope [ 28 ]. It is essential that palliative care professionals perceive themselves as potential influencers and explicitly transmit the reasons for their intervention [ 29 ] while avoiding perpetuating myths, misunderstandings, and positive associations with a lack of palliative care. HPs should grasp the chance to carry out these sharing procedures when a decision is required.…”
Section: Discussionmentioning
confidence: 99%
“…Better education of the young university population, who may involuntarily perpetuate stigmas, can therefore be of great value in improving their potential engagement. Palliative practitioners are key actors in dealing with possible misunderstandings and building a discourse to promote greater and better understanding and to cease perpetuating myths, misunderstandings, and a negative reputation for PC (Reigada et al, 2021a). A palliative care-protective public discourse must accompany this comprehensive and global transmission of palliative care in young university students (O'Connor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For patients, this means being acknowledged in all aspects of their Professional commitment to the patient and family carers: present and future personhood, 56 for family carers it manifests through their active participation in care and decision-making, 57 while for professionals it is about successfully communicating all that they and the palliative care service can offer. 58…”
Section: Main Findings Of the Studymentioning
confidence: 99%